Study of low earth orbit ultraviolet radiation and vacuum thermal cycling environment effects on epoxy-based shape memory polymer. (November 2019) - Tan, Qiao; Li, Fengfeng; Liu, Liwu; Liu, Yanju; Yan, Xiangqiao; Leng, Jinsong
Shape memory polymers have been studied as the matrix of lightweight self-deployable space structures for decades. The epoxy-based shape memory polymer, which is a potential material for aerospace application, has been tested about their resistance abilities to the ultraviolet radiation and vacuum thermal cycling by using ground-based simulation facilities. The wavelength of ultraviolet radiation is 250–400 nm with not less than five times the solar constant, and the irradiation times are 80, 160, and 240 h, respectively. The vacuum level, temperature range, and cycling times of vacuum thermal cycling are 10 −5 Pa; −100°C to +100°C; and 0 cycle and 15, 30, and 45 cycles, respectively. The shape memory polymer specimens are compared for mass loss ratio, chemical compositions, surface morphology, and mechanical properties before and after the ultraviolet radiation and thermal cycling. The experimental results indicate that the glass transition temperature (Tg ), mass loss ratio, modulus, and yield and break strength increase after experiencing 240h ultraviolet radiation or 45 thermal cycles, which shows great potential of epoxy-based shape memory polymer in aerospace structures and device applications.